Valère du Bierzo. Écrits autobiographiques et de l’au-delà. Texte établi, traduit et commenté par P. Henriet (coord.), J. Elfassi, F. Gallion, C. Martin et J. C. Martín-Iglesias - Codoñer Merino, Carmen (Revista de Estudios Latinos, 2022)
Valère du Bierzo. Écrits autobiographiques et de l’au-delà. Texte établi, traduit et commenté par P. Henriet (coord.), J. Elfassi, F. Gallion, C. Martin et J. C. Martín-Iglesias, Paris, Les Belles Lettres, 2021.